Use of cloud-based accounting technologies in the information security system - Sokolenko, Liudmyla; Соколенко, Людмила; Egorushkina, Tatyana; Єгорушкіна, Тетяна; Kosytsia, Olha; Косиця, Ольга; Atamas, Oleksandr; Атамас, Олександр Петрович; Kyiashko, Olha; Кияшко, Ольга (Academy of Accounting and Financial Studies, AAFSJ, 2020)
The existing standards in the field of creation of cloud information-and-computing systems were studied, main issues related to the use of cloud technologies were determined. The models of architectural levels of the computing cloud spread in the world were considered, and their advantages and disadvantages were determined. Their characteristics were compared with the indication of the degrees of implementation and functional capabilities. The international standards have mainly conceptual-recommendation nature and do not take into account main factors, which significantly influence the accuracy and objectivity of risk evaluation. When introducing cloud technologies, one should have a strategic plan that will help to correctly set goals and see their achievement, control and coordinate the movement to the result achievement. The issue of the development of ITstrategy of introduction is in that it is important to determine, as early as at the stage of its formation, which models of formation of risks of data loss will satisfy the corporation when transferring to the cloud environment, evaluate providers of cloud services in terms of reliability and safety. The paper describes aspects of use of cloud technologies in accounting, the analysis of their application in the world practice and by business has been performed. The substantial attention has been paid to the characteristics of advantages and disadvantages of use of cloud technologies in business and accounting, in particular. Досліджено існуючі стандарти у сфері створення хмарних інформаційно-обчислювальних систем, визначено основні питання використання хмарних технологій. Розглянуто моделі архітектурних рівнів поширення обчислювальної хмари у світі, визначено їх переваги та недоліки. Їх характеристику порівнювали із зазначенням ступенів реалізації та функціональних можливостей. Міжнародні стандарти мають переважно концептуально-рекомендаційний характер і не враховують основні чинники, які суттєво впливають на точність та об'єктивність оцінки ризиків. При впровадженні хмарних технологій необхідно мати стратегічний план, який допоможе правильно поставити цілі та побачити їх досягнення, контролювати та координувати рух до досягнення результату. Проблематика розробки ІТ-стратегії впровадження полягає в тому, що важливо ще на етапі її формування визначити, які моделі формування ризиків втрати даних задовольнять корпорацію при переході в хмарне середовище, оцінити провайдерів. хмарних сервісів з точки зору надійності та безпеки. У статті описано аспекти використання хмарних технологій в бухгалтерському обліку, проведено аналіз їх застосування у світовій практиці та бізнесі. Значну увагу приділено характеристиці переваг та недоліків використання хмарних технологій у бізнесі та бухгалтерському обліку, зокрема.
Використання хмарних технологій бухгалтерського обліку в системі захисту інформації
Keywords: Cloud Computing; Хмарні обчислення; Information Technologies; інформаційні технології; Digitation of Reporting; оцифровка звітності; Analytic Hierarchy Process; аналітичний ієрархічний процес; Information Safety; інформаційна безпека